2014
DOI: 10.1002/cphc.201402615
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Properties of CoGen (n=2–11) Clusters: Photoelectron Spectroscopy and Density Functional Calculations

Abstract: A series of cobalt-doped germanium clusters, CoGe(n)(-/0) (n=2-11), are investigated by using anion photoelectron spectroscopy combined with density functional theory calculations. For both anionic and neutral CoGe(n) (n=2-11) clusters, the critical size of the transition from exo- to endohedral structures is n=9. Natural population analysis shows that there is electron transfer from the Ge(n) framework to the Co atom at n=7-11 for both anionic and neutral CoGe(n) clusters. The magnetic moments of the anionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
73
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 53 publications
4
73
1
4
Order By: Relevance
“…This also indicates that the electron transfer from the Ge n framework to the Ti atom is strongly related to the structural evolution of TiGe n clusters, especially related to the formation of endohedral structures. In addition, this electron transfer pattern is similar to those of CoGe n −/0 (n=2−11) [26] and VGe n −/0 (n=3−12) [27] clusters, but different from those of the CuGe n (n=2−13) [20], and NiGe n (n=1−20) [32] clusters, in which the electron transfers from the Cu or Ni atom to the Ge n framework. As shown in Table III, the total magnetic moments of the anion TiGe n − (n=7−12) clusters are 1 µ B .…”
Section: Discussionmentioning
confidence: 72%
“…This also indicates that the electron transfer from the Ge n framework to the Ti atom is strongly related to the structural evolution of TiGe n clusters, especially related to the formation of endohedral structures. In addition, this electron transfer pattern is similar to those of CoGe n −/0 (n=2−11) [26] and VGe n −/0 (n=3−12) [27] clusters, but different from those of the CuGe n (n=2−13) [20], and NiGe n (n=1−20) [32] clusters, in which the electron transfers from the Cu or Ni atom to the Ge n framework. As shown in Table III, the total magnetic moments of the anion TiGe n − (n=7−12) clusters are 1 µ B .…”
Section: Discussionmentioning
confidence: 72%
“…However, as the size of cluster increasing, finding the global minimum geometries becomes increasingly difficult due to the much increased complexity of the potential surface as well as the rapid increase of the number of low-lying isomers 5 6 . Luckily, the combined experimental and theoretical photoelectron spectroscopy approach has become a very effective method to identify the cluster structures, which has successfully determined the true global-minimum structures for various clusters ranging from small or medium-sized cluster to large sized cluster 7 8 9 10 11 12 .…”
mentioning
confidence: 99%
“…However, pure germanium clusters can not form stable fullerene-like cage structures and are unsuitable as a building block of self-assembly materials 15 16 . In order to generate and stabilize Ge cage structures, numerous experimental and theoretical investigations have been performed on transition metal (TM)-doped germanium clusters, similar to the case of TM-doped silicon clusters 11 12 17 18 19 20 21 22 23 24 25 . It is found that the TM-doped germanium clusters reveal different growth pattern from the TM-doped silicon clusters 19 26 .…”
mentioning
confidence: 99%
“…The physical and chemical properties of transition metal‐doped germanium clusters are determined by their size, shape, and composition. In the literature, we can see a large amount of experimental and theoretical investigations on the structures of transition metal‐doped germanium clusters . It is found that doping of transition metal to pure germanium clusters can form stable cage structures that can be used as building blocks for synthesis novel materials …”
Section: Introductionmentioning
confidence: 99%